2022
DOI: 10.3390/met12030486
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Liquation and Segregation Induced Failure Mechanism in Thick Dissimilar Aluminum Alloy Electron-Beam Welds

Abstract: This study presents new findings on the underlying failure mechanism of thick dissimilar electron-beam (EB) welds through a study on the AA 2219-AA 5083 pair. Contrary to the prior studies on EB welding of thin Al alloys, where liquation in the grain boundaries (GBs) in the partially melted zone (PMZ) was not observed, the present investigation for thick EB welds reports both liquation and increased segregation of Cu in the PMZ. The work is thus directed towards understanding the unusual observation in the PMZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This indicates that joints are free of defects and the achieved joint efficiency is around 100% (based on alloy AA5182). This is much higher than what can be achieved with electron beam [5,32,33] and TIG [8] welding processes. The presented data agree with the results obtained in dissimilar FSWed joints of AA2219 and AA5083 [6,13,14,[16][17][18].…”
Section: Tensile Testsmentioning
confidence: 67%
“…This indicates that joints are free of defects and the achieved joint efficiency is around 100% (based on alloy AA5182). This is much higher than what can be achieved with electron beam [5,32,33] and TIG [8] welding processes. The presented data agree with the results obtained in dissimilar FSWed joints of AA2219 and AA5083 [6,13,14,[16][17][18].…”
Section: Tensile Testsmentioning
confidence: 67%
“…In addition, there were some θ-Al 2 Cu particles in the WZ and Al-Cu eutectic in the HAZ. Mastanaiah et al found that the θ-Al 2 Cu particles precipitated from α-Al matrix destroyed the integrity and induced the initiation of cracks during the deformation process [17]. Thus, the 2219 joint showed a lower elongation.…”
Section: Mechanical Properties Of 2219 Jointmentioning
confidence: 99%
“…Fujii et al [16] investigated the relation between pores and bubble generation. He found that the bubbles were formed through a reaction between the molten Al and Al 2 O 3 forming Al 2 O. Mastanaiah et al [17] reported that the extensive liquation and segregation of Cu in the partially melted zone (PMZ) increased in the thick-plate EBW, which resulted in the failure of PMZ on the 2219Al side of the 2219/5083 joint. S.A. Hosseini et al [11] evaluated the hot cracking sensitivity of 2024 joint by EBW and investigated the effects of heat input on the hot cracking.…”
Section: Introductionmentioning
confidence: 99%